Shema’s Beauty Saloon / Rafidah Kasim ... [et al.] - Kasim, Rafidah; Abd Rahman, Norazatulshima; Mohd Silam, Siti Nor Aeishah Rani; Saari, Norazimah; Awalludin, Izatol Afizah (2001)
Shema’s Beauty Saloon is the company that provide beauty service to all type of people. This include facial, body and hair treatment. This company is located in City Plaza Shopping Complex which is situated in the middle of Alor Setar.